The Legal Issues Concerning the Operation of Fin-Tech in Nigeria - Aidonojie, Paul Atagamen; Majekodunmi, Toyin Afolabi; Adeyemi-Balogun, Omolola Janet (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Technology has greatly enhanced the developmental process of the global environment. It suffices to state that, Nigeria being a developing country is also having its fair share in the use of technology within the financial sector. This is concerning the fact that the traditional method of financial activities is gradually overtaken by financial technology. However, despite the prospect of finance and technology (Fin-Tech), there are several legal issues and challenges affecting its operation in Nigeria. In this regard, this study tends to embark on a hybrid method of study on the prospect and legal issues concerning Fin-Tech in Nigeria. The questionnaire was distributed to 301 respondents residing within Nigeria. The data obtained was analysed through descriptive and analytical statistical methods. The study, therefore, found that the introduction of Fin-Tech has greatly enhanced the commercial sector in Nigeria. Although, several challenges include the legality of its operations, other social and economic challenges could affect its smooth operation. The study concluded and recommended the necessity for legal regulations, internet security, educating the general public on the Fin-Tech system, and alignment of Fin-Tech operations with Nigerian laws for a smoother adoption of Fin-Tech in Nigeria.